Prevalence and Clinicopathologic Features of Canine Metastatic Melanoma Involving the Central Nervous System: A Retrospective Analysis and Comparative Review - Razmara, Aryana M.; Wittenburg, Luke A.; Al-Nadaf, Sami; Toedebusch, Ryan G.; Meyers, Frederick J.; Toedebusch, Christine M. (Frontiers in Oncology, 2022)
Background: Central nervous system (CNS) involvement is the leading cause of death in malignant melanoma. Rodent models, while vital to mechanistic investigation, have had limited success identifying effective therapies for melanoma brain metastases. The companion dog with de novo melanoma is a promising complementary model for developmental therapeutic investigation, as these tumors occur in an immunologically outbred host that has shared environmental exposures with humans. However, relatively little is known regarding the prevalence and clinicopathological features of canine melanoma metastasis to the CNS. To further validate the dog as an appropriate model for human metastatic melanoma, the aims of this study were to determine the rate of CNS metastasis and associated clinicopathologic features in canine malignant melanoma. Methods: Medical records of dogs diagnosed with malignant melanoma from 1985-2019 at the University of California Davis Veterinary Medical Teaching Hospital were assessed retrospectively. Clinicopathologic features were compared between dogs with CNS metastasis (CNS+) and dogs without CNS metastasis (CNS-). Site of CNS involvement and associated neurological signs were analyzed via Wilcoxon-Mann-Whitney rank sum and Fisher’s exact tests. Survival data were analyzed via Kaplan-Meier estimates. Results: CNS metastasis was identified in 38% of dogs in this study (20/53). The oral cavity was the most common site of primary melanoma in both groups (CNS+: n=12 (60%) vs. CNS-: n=22 (67%); p>0.99). The total burden of metastatic disease was higher in the CNS+ group (CNS+: 4, 95% CI 3-5 vs. CNS-: 3, 95% CI 1-3; p<0.001). The cerebrum was the most common site of CNS metastasis (n=15, 75%) and seizures were the most observed neurological sign (n=9, 64%). There was no difference in overall survival between CNS+ and CNS- groups. However, the median survival time following onset of neurological signs was 9.5 days (95% CI 1-43), with 5 dogs euthanized within 24 hours of the onset of neurological signs. Conclusions: Canine and human MM patients share similar rates of CNS metastasis and clinical presentation. This study will guide clinical management of canines with malignant melanoma and inform future studies using dogs with spontaneously occurring melanoma as a preclinical model for human melanoma brain metastases.